If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(7-5)=6(4x-2)
We move all terms to the left:
4(7-5)-(6(4x-2))=0
We add all the numbers together, and all the variables
-(6(4x-2))+42=0
We calculate terms in parentheses: -(6(4x-2)), so:We get rid of parentheses
6(4x-2)
We multiply parentheses
24x-12
Back to the equation:
-(24x-12)
-24x+12+42=0
We add all the numbers together, and all the variables
-24x+54=0
We move all terms containing x to the left, all other terms to the right
-24x=-54
x=-54/-24
x=2+1/4
| 10+8r=4r+20 | | 2x^2-12=108 | | 13=14a | | 4(7-5)=6(4x-2 | | 18=m-10 | | -8y+3(y-4)=18 | | 52+(3n+5)=71 | | 2/3(6x-3/2)=3-x | | -7(1-6x)-6x=6(x-7)+5 | | 6(v+6)-8v=20 | | y=y^2−3y | | 78.75+80.25x=40+90.75x | | (8h+2)^2-1515;h=3 | | a+20=37 | | 72=6(x+6) | | 90=1.8c+32 | | 7(p+8)+4=81 | | 32-8-12x=11(2x-6) | | 2t−–2=10 | | 4(x-7)-6x=-24 | | 10+7/45=x | | 7x-12=5x-1 | | 18+n=36 | | 9(n–4)=45 | | -4-14y=2(7y-16) | | x-(-7-4x)=8 | | y=372000(1.05)^6 | | -8w+4(w-5)=-28 | | y=-5+2.5 | | 2x1=0 | | 2(w)+2(w+12)=68 | | -5/4p-1/2=-3/4+5/8p |